A Study On The Relationship Of Positive Attitudes Towards Employee In A Multinational Company - Muniandy, Nirmala (2009)
All business, no matter how large or small has more than a few things in common. Both corporate conglomerates with thousands of workers and the business that employs fewer than 50 have the same competitive advantage, people. Many business executives and owners are beginning to realize that the only true sustaining competitive advantage they can hope to achieve is through their people. The purpose of present study is to determine the relationship of positive attitudes (motivation, organizational commitment, punctuality and self confidence) and productive employee attitudes (fluency of expression, innovation, sense of humour and leadership).